Unmasking Disseminated Histoplasmosis Immune Reconstitution with Adrenal Insufficiency in a HIV Infected on HAART - MN, Dr ARVIND; Bhat, Dr Bhargav V; N, Monika (International Journal of Innovative Research in Medical Science, 2022)
Histoplasmosis is a fatal but rare infection caused by Histoplasma Capsulatum which is Dimorphic fungi found in soil. Incidence of Histoplasmosis is in HIV infected is around 2-5% while its only <0.05% in Non-HIV infected Individuals. In our case Patient with initial CD4 Counts of 22 was started on HAART therapy after ruling out common opportunistic infections like Tuberculosis etc. 7 months later patient presented with Features suggestive of Adrenal insufficiency (Fever, Diarrhea , vomiting , Dizziness, Hypotension confirmed with relevant tests) . Chest X-ray revealed B/L Nodular opacities and Lymph node biopsy Suggested Intranuclear yeast like inclusions s/o Histoplasmosis. Patient was treated with Liposomal Amphotericin B for 10days which showed complete resolution of Chest X-ray B/L nodular opacities along with Clinical Improvement and Patient was later discharged